Impact of Self Service Technology Quality on Customer Satisfaction: A Case of Retail Banks in Western Province in Sri Lanka - H.M.R.S.S., Gunawardana; Kulathunga, D.; Perera, W.L.M.V. (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2015)
Rapid technological advancement in the banking environment drives Sri Lankan banks to adopt self-service technologies to deliver services via SMS banking, Internet banking and telephone banking facilities, Automated Teller Machines (ATM) etc. This study explored the perceived quality of the self-service technology of these services and its effect on customer satisfaction. The literature survey and in depth interviews helped to formulate quality dimensions: security, efficiency, eases of use, reliability and convenience and those dimensions were assessed through a questionnaire. This study surveyed 215 customers from branches of six dominating commercial banks located in Western Province of Sri Lanka. Data were subjected to Principal Component Analysis and retained factors were regressed using multiple regressions to assess the impact of quality dimensions on customer satisfaction. The results revealed that reliability and convenience have positive impacts on customer satisfaction but efficiency has a negative effect.